2016
DOI: 10.1002/aic.15585
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced performance of Rh1/TiO2 catalyst without methanation in water‐gas shift reaction

Abstract: Water‐gas shift (WGS) reaction is an important process for industrial hydrogen production. The side reaction of methanation often causes unavoidable loss of H2 along with this reaction. Here, we report a Rh1/TiO2 single‐atom catalyst (SAC) with appreciable loading of 0.37 wt %, which exhibited an overall CO conversion of ∼95% but without any methanation at 300°C, even under CO2‐ and H2‐rich WGS stream. The specific activity of this SAC was around four times higher than that of cluster catalyst, which meanwhile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 83 publications
(60 citation statements)
references
References 40 publications
4
55
0
1
Order By: Relevance
“…These results illustrate that Pd single-atoms exhibit higher atomic efficiency than its cluster counterpart, which is in harmony with previous work on Ir and Rh metals. 16,39 In comparison with Pd/Al 2 O 3 and other reported Pd catalysts, such as Pd/TiO 2 , 35 Pd/MnO 2 , 36 Pd@CeO 2 /Al 2 O 3 , 37 Pd/ CeO 2 , 38 our catalyst is times or orders of magnitude more active but with lower Pd loadings. Moreover, this activity is comparable with those values of the former reported Ir, Rh single atoms despite different loading amount or support type.…”
Section: Catalytic Performance In Wgs Reactionmentioning
confidence: 59%
See 1 more Smart Citation
“…These results illustrate that Pd single-atoms exhibit higher atomic efficiency than its cluster counterpart, which is in harmony with previous work on Ir and Rh metals. 16,39 In comparison with Pd/Al 2 O 3 and other reported Pd catalysts, such as Pd/TiO 2 , 35 Pd/MnO 2 , 36 Pd@CeO 2 /Al 2 O 3 , 37 Pd/ CeO 2 , 38 our catalyst is times or orders of magnitude more active but with lower Pd loadings. Moreover, this activity is comparable with those values of the former reported Ir, Rh single atoms despite different loading amount or support type.…”
Section: Catalytic Performance In Wgs Reactionmentioning
confidence: 59%
“…It was previously confirmed that the abundant oxygen vacancies formed by the promotion of single-atoms were responsible for the adsorption and dissociation of H 2 O to generate H 2 . 39 The TOF value based on the surface FeO x sites with neighbor of Pd is also higher on 0.044 wt % Pd/FeO x (0.45 s 21 ) than on 1.1 wt % Pd/FeO x (0.23 s 21 ) as [Color figure can be viewed at wileyonlinelibrary.com] Figure 11. XRD patterns of the fresh, the CO reduction and the H 2 O oxidation 0.044 wt % Pd/FeO x catalysts, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Moderately enhanced tof compared to supported NPs has also been demonstrated over SACs of other metals,including Ir 1 /FeO x (2.6 times) [84] and Rh 1 /TiO 2 (4 times). [85] The continued debate over the most effective species likely reflects the need for improved control in the synthesis of supported subnanometer metal structures.U nfortunately, most comparisons have been made over catalysts with significantly different metal contents,which could also impact the specific interaction with the host and hence the generality of the conclusions derived. Although strategies to promote the metal-specific activity are known, practically the choice of host is likely to be critical since it will influence the maximum loading capacity of aS AC.T od ate,t here is limited understanding of the distribution and stability of atomically dispersed species.Inthe case of inert supports,little is known about the scope of the stabilization with alkali/alkaline-earth metal additives.S ynergies between the host and the active metal-as predicted for Pt 1 /Mo 2 C-could also be exploited.…”
Section: Methodsmentioning
confidence: 99%
“…Wet chemical routes, such as incipient wetness impregnation (IWI) and strong electrostatic adsorption methods, are common in laboratory-scale catalyst synthesis. However, they are best suited to low metal loadings 1,35,36 and are often time-consuming and process intensive, which is unfavorable for scale-up 18,37 . In addition, the thermal stability of the resulting SACs is typically poor 18,35 .…”
mentioning
confidence: 99%